2018
DOI: 10.12973/ijem.4.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of Innovative Learning Model toward Critical Thinking Ability

Abstract: The aim of this study is to investigate teachers' perceptions about the importance of learning innovation toward critical thinking ability in learning mathematics. The subjects in this study are the teachers and the students of grade Vin Al-Islam 6 Al-Fajar, Muhammadiyah 23 and Cokroamino to Islamic Elementary School Surakarta. The research method used in this research is qualitative case study. The problem in the research is the students' mathematics score is low that is seen from the results of the daily tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 4 publications
1
15
0
1
Order By: Relevance
“…As mathematics is one of the core and essential subjects of the Malaysian curriculum, the approach emphasized should help teachers and students in that the application of CTS practice does not interfere with existing curriculum requirements. One of the best steps is to apply the elements of HOTS in every teaching process to produce students who are highly creative and able to think critically (Munawaroh et al, 2018). Therefore, teachers need first to have a high level of perception and readiness in the application of CTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mathematics is one of the core and essential subjects of the Malaysian curriculum, the approach emphasized should help teachers and students in that the application of CTS practice does not interfere with existing curriculum requirements. One of the best steps is to apply the elements of HOTS in every teaching process to produce students who are highly creative and able to think critically (Munawaroh et al, 2018). Therefore, teachers need first to have a high level of perception and readiness in the application of CTS.…”
Section: Discussionmentioning
confidence: 99%
“…In mathematics, the application of CTS is usually more inclined to the skills of analyzing arguments, making inferential analysis either through inductive or deductive reasoning methods, performing assessments, and making accurate decisions from existing problems (Ismail et al, 2019;Munawaroh et al, 2018). Therefore, students who can think critically will have a high level of scientific thinking and can perform work very systematically.…”
Section: Theory and Concept Of Critical Thinking Skillsmentioning
confidence: 99%
“…As a matter of fact, application, analysis, and evaluation-oriented learning experiences all develop problem-solving, inferencing, estimation, generalization and creative thinking skills, which are considered higher-order thinking skills (Wilks, 1995). In Bloom"s taxonomy, critical thinking success in the learning process occurs when students can perform at the levels of analysis, synthesis and evaluation (Munawaroh, Sudiyanto & Riyadi, 2018). Especially in the face of changes and advances in the digital age, individuals need to be successful in choosing the appropriate information, analyzing, synthesizing and transferring it to new experiences by catching the latest developments (Akpur, 2020).…”
Section: High Level Thinking Skillmentioning
confidence: 99%
“…Literature in the context of mathematical intuition and logic showed that formal schooling has not provided students with structured opportunities to practice and develop creative and critical thinking in the subject of mathematics (Thibaut et al, 2018). Educators often believe that logical thinking is significant for learning math, while creativity is viewed to be less significant (Munawaroh, 2018). Nevertheless, mathematics is linked with science, and scholars apply creative thinking when confronted with new challenges (Pirrone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%